Enhancing Early Childhood Cognitive Development through Play-Based Learning: A Case Study - Joseph Zuva; Christopher Mutseekwa; John R. Slate; Bendraou Rachid; Muhini L. Kahare; James P. Takona (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: This study examines cognitive development in early childhood within the context of play-based learning at Al-Hidayah Kindergarten. Grounded in constructivist perspectives, the research emphasizes that cognitive development in early childhood is shaped not merely by stimulus–response mechanisms, but by children’s active engagement and individual learning processes. Accordingly, learning processes are considered more critical than final outcomes, given the variability in children’s cognitive developmental trajectories. Aims and scope of paper: The study aims to explore how structured play activities—specifically puzzle-solving and block-stacking—support cognitive learning processes, including problem-solving and creativity, in a preschool setting. It also investigates the implementation of group-based learning models and identifies challenges encountered in fostering cognitive development through play. Methods: A qualitative research design was employed, with data collected through classroom observations and semi-structured interviews with teachers. The analysis focused on children’s interactions during play activities and how these interactions reflected their cognitive development. Results: The findings indicate that play-based learning significantly supports the development of children’s cognitive abilities, particularly in problem-solving and creative thinking. Nevertheless, several challenges were identified, including children’s tendency to lose interest quickly and the emergence of egocentric behaviors, such as limited willingness to share and cooperate with peers. Contribution: This study contributes to the global discourse on early childhood education by providing empirical insights into how play-based learning and responsive pedagogical strategies support cognitive development in preschool settings. It extends existing literature by illustrating the interplay between cognitively enriching play activities and children’s behavioral responses within everyday classroom contexts. By identifying both enabling factors and behavioral challenges inherent in play-based learning environments, this study offers transferable pedagogical implications for early childhood educators seeking to enhance the effectiveness of instructional practices across diverse educational contexts.